COMPARATIVE ANALYSIS OF SMART ECONOMY STRATEGIES IN EMPOWERING SMALL AND MEDIUM ENTERPRISES IN INDONESIA - Sharon Sheilla Shane; Wilmaya Firmanditiyas; Gabriella Paulita Morong; Master Edison Siregar (Yayasan Amanah Nur Aman, 2026)
The Smart City concept has become a dominant paradigm in Indonesia's urban development, with the Smart Economy pillar playing a vital role in empowering Micro, Small, and Medium Enterprises (MSMEs) as the backbone of the national economy. However, the implementation of this concept reveals significant disparities across regions. This study aims to comparatively analyze Smart Economy implementation strategies in three major cities: DKI Jakarta, Surabaya, and Medan, and identify the determinants of their success and failure. This research employs a qualitative approach using a comparative document study method. Data were collected through the analysis of policy documents, government reports, and relevant scientific publications, without conducting field interviews. The results indicate three distinct models: (1) DKI Jakarta successfully implements a digital ecosystem integration model through the Jakpreneur program linked within the JAKI super-app; (2) Surabaya succeeds with a community-based economic resilience model through the e-Peken market policy innovation, which mandates civil servants to purchase from local MSMEs; and (3) Medan continues to face challenges regarding inter-agency policy fragmentation and low digital readiness among business owners. The study concludes that the success of a Smart Economy is not solely determined by advanced technology adoption, but by leadership that translates vision into concrete market policies, the existence of a centralized orchestration platform, and an institutionalized collaborative ecosystem. These findings recommend that developing cities like Medan prioritize service platform integration and market intervention policies prior to pursuing mass digitalization.